2017
DOI: 10.1007/s00284-016-1159-9
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Di(2-Ethylhexyl) Phthalate by a Novel Gordonia alkanivorans Strain YC-RL2

Abstract: One bacterial strain, YC-RL2, isolated from petroleum-contaminated soil, could utilize environmental hormone Di(2-Ethylhexyl) phthalate (DEHP) as a sole carbon source for growth. Strain YC-RL2 was identified as Gordonia alkanivorans by 16S rRNA gene analysis and Biolog tests. The effects of environmental factors which might affect the degrading process were optimized at 30 °C and pH 8.0. Strain YC-RL2 showed superior halotolerance and could tolerate up to 0-5% NaCl in trace element medium supplemented with DEH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
69
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(75 citation statements)
references
References 55 publications
6
69
0
Order By: Relevance
“…It consisted of 10.0 g l − 1 peptone, 5.0 g l − 1 yeast extract, and 10.0 g l − 1 NaCl. (2) Trace Elements Medium (TEM) as described by [48] were used for isolation of BPA biodegradable strains and statistical optimization experiments.…”
Section: Chemicals and Mediummentioning
confidence: 99%
“…It consisted of 10.0 g l − 1 peptone, 5.0 g l − 1 yeast extract, and 10.0 g l − 1 NaCl. (2) Trace Elements Medium (TEM) as described by [48] were used for isolation of BPA biodegradable strains and statistical optimization experiments.…”
Section: Chemicals and Mediummentioning
confidence: 99%
“…It consisted of 10.0 g l −1 peptone, 5.0 g l −1 yeast extract, and 10.0 g l −1 NaCl. (2) Trace Elements Medium (TEM) as described by [32] were used for isolation of BPA biodegradable strains and statistical optimization experiments.…”
Section: Chemicals and Mediummentioning
confidence: 99%
“…Samples (20 ml) were taken in triplicate each 8 hours intervals as following (8,16,24,32,40,48,56 and 64 hours) and centrifugated at 15000 rpm for 30 minutes to eliminate the bacterial cells. The cellfree supernatant was kept at -20 °C.…”
Section: Bpa Degradation At Low and High Concentrations And Total Orgmentioning
confidence: 99%
“…[22,23]. Previous studies on the degradation pathways of DEHP have shown that DEHP may be converted to MEHP through esterase hydrolysis, then further hydrolyzed to PA, and finally gradually mineralized [24][25][26]. It has also been reported that the DEHP degradation pathway is that DEHP first shortens the side chains by β-oxidation to form medium-chain DBP, then hydrolyzes into short-chain DEP and finally converts into PA [27].…”
Section: Introductionmentioning
confidence: 99%